2022
DOI: 10.1177/03635465221083610
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs Reduce Therapeutic Efficacy of Mesenchymal Stromal Cell Therapy in a Rodent Model of Posttraumatic Osteoarthritis

Abstract: Background: Intra-articular injections of human mesenchymal stromal cells (hMSCs) have shown promise in slowing cartilage degradation in posttraumatic osteoarthritis (PTOA). Clinical use of cell therapies for osteoarthritis has accelerated in recent years without sufficient scientific evidence defining best-use practices. Common recommendations advise patients to avoid nonsteroidal anti-inflammatory drug (NSAID) use before and after cell injection over concerns that NSAIDs may affect therapeutic efficacy. Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…A single dose of NSAID was administered for animal welfare reasons, to avoid unnecessary pain and swelling due to the needle insertion all animals treated with intralesional injection (IVP and CP). The use of NSAIDs could potentially have a negative impact on the potency of MSCs ( 45 , 46 ), however It is unclear whether the concomitant use of NSAIDs interferes with the working mechanism of the tpMSCs. In the previously performed clinical field trial efficacy was demonstrated for tpMSC in naturally occurring tendon and ligament injuries, with statistically significant differences in all clinical and ultrasonographical parameters between the groups, as well as by significantly lower reinjury rate in tmMSCs treated horses in the long term ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of NSAID was administered for animal welfare reasons, to avoid unnecessary pain and swelling due to the needle insertion all animals treated with intralesional injection (IVP and CP). The use of NSAIDs could potentially have a negative impact on the potency of MSCs ( 45 , 46 ), however It is unclear whether the concomitant use of NSAIDs interferes with the working mechanism of the tpMSCs. In the previously performed clinical field trial efficacy was demonstrated for tpMSC in naturally occurring tendon and ligament injuries, with statistically significant differences in all clinical and ultrasonographical parameters between the groups, as well as by significantly lower reinjury rate in tmMSCs treated horses in the long term ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the immunomodulatory effect of MSCs depends on the severity of tissue inflammation [ 137 , 138 , 139 , 140 , 141 ]. Another factor that can influence the study are NSAIDs, which were described as inhibitors of MSCs in vitro [ 142 ] and in vivo [ 143 ]. NSAIDs inhibit proliferation, differentiation, and migration of MSCs [ 144 , 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicates Proposed immune interactions of MSCs with host immune cells that lead to anti-inflammatory phenotype, the release of endogenous opioids, and pain relief. that the use of NSAIDs reduces the therapeutic efficacy of MSCs in a rodent OA model (136), suggesting a role of inflammatory response in MSC's beneficial effect. Thus, MSCs-produced pain relief is underlain by sophisticated reciprocal interactions between implanted cells and immune cells and the involvement of both pro-and anti-inflammatory mediators and their receptors.…”
Section: Role Of Immune Mediatorsmentioning
confidence: 97%